1971
DOI: 10.1071/ch9710303
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II) and platinum(II) complexes of 2,9-Dimethyl-1,10-phenanthroline. I. Halide compounds

Abstract: Complexes of 2,9-dimethyl-1,10-phenanthroline with palladium(II) and platinum(II) halides are described. The methyl groups of the ligand introduce strong steric hindrance in some of the normal geometries of these transition-metal complexes, and evidence is presented for five- coordination in the bis(dmp) compounds of these two metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…3 1 P nuclear magnetic arrangement (1 1. The existence of five coordinate resonance spectra were recorded at 40.5 MHz in dichlorocomplexes of platinum(I1) has also been reported methane solution using H , P o 4 as external reference on on the basis of spectroscopic (2)(3)(4)(5) and X-ray a Varian XL-100 spectrometer with noise decoupling of diffraction (6-7) studies. In view of the rarity of P r~t O s~; e s of Weisanberg and Precession photographs five coordinate platinun~ complexes cveconsidered obtained using ~~~~~~d i~ ~h~ space group it of interest to undertake a crystal structure study P2,/c was established unequivocally from the systematic of (PtCl(phen)(PEt,),)(BF,), since conductance and proton magnetic resonance studies had suggested a five-coordinate structure as the most likely for this complex in solution (8).…”
mentioning
confidence: 99%
“…3 1 P nuclear magnetic arrangement (1 1. The existence of five coordinate resonance spectra were recorded at 40.5 MHz in dichlorocomplexes of platinum(I1) has also been reported methane solution using H , P o 4 as external reference on on the basis of spectroscopic (2)(3)(4)(5) and X-ray a Varian XL-100 spectrometer with noise decoupling of diffraction (6-7) studies. In view of the rarity of P r~t O s~; e s of Weisanberg and Precession photographs five coordinate platinun~ complexes cveconsidered obtained using ~~~~~~d i~ ~h~ space group it of interest to undertake a crystal structure study P2,/c was established unequivocally from the systematic of (PtCl(phen)(PEt,),)(BF,), since conductance and proton magnetic resonance studies had suggested a five-coordinate structure as the most likely for this complex in solution (8).…”
mentioning
confidence: 99%
“…In [5], none of the four ligand halves are equivalent, and in [6] there are three distinct chemical and magnetic environments for the halves of each ligand. The proposed structure [7] with the halide atom in the trigonal plane gives rise to two environments and indeed there are only two sets of signals observed in the n.m.r, spectra of the compounds.…”
Section: D) Pd(dmp)2x2 (X = CL Br)mentioning
confidence: 94%
“…The three possible geometries proposed (7) for these fivecoordinate compounds are shown in [5]- [7]. It should be noticed that [5] imposes the most steric strain of the three structures.…”
Section: D) Pd(dmp)2x2 (X = CL Br)mentioning
confidence: 99%
“…It was found that bischelate complexes like [Pd(2,9-Me 2 -phen) 2 X 2 ] exist in solutions as five-coordinate easily dissociating cations [Pd(2,9-Me 2 -phen) 2 X] + [125].…”
Section: Ligand−receptor Interactions In Square-planar Complexes [M(nmentioning
confidence: 99%